Finite-Time Stability of Impulsive Fractional-Order Time Delay Systems with Damping Behavior - examples., This work made for analyzing the finite-time stability of impulsive nonlinear delay damped system with caputo fractional derivative of orders; . Sufficient conditions which are derived from extended form of Gronwall's inequality to analyze the stability in the finite range of time for such multi-term fractional-order impulsive control system. The potential of the proposed approach is demonstrated with the support of two numerical (Discontinuity, Nonlinearity, and Complexity, 2026)
This work made for analyzing the finite-time stability of impulsive nonlinear delay damped system with caputo fractional derivative of orders α_1(1,2] and α_2(0,1]. Sufficient conditions which are derived from extended form of Gronwall’s inequality to analyze the stability in the finite range of time for such multi-term fractional-order impulsive control system. The potential of the proposed approach is demonstrated with the support of two numerical examples.